ASSOCIATION OF HIGH PLASMA HOMOCYSTINE AND TOTAL SERUMCHOLESTEROL LEVELS WITH ACUTE ISCHEMIC STROKE (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Stroke or cerebrovascular accidents ranks first in frequency and emergency among all neurological disorders. Incidence of stroke is coming down in western countries while it is showing an alarming rise in India. Raised homocysteine and serum cholesterol is associated with atherosclerotic vascular events. Aims and Objective: Present study was carried out to find association between high plasma homocystine and total serum cholesterol levels with acute ischemic stroke. Materials and Methods: Study included 30 diagnosed cases of acute ischemic stroke (20 Male and 10 Females) and 30 controls (20 Male and 10 Females) of same age and sex. Blood sample of cases and controls was collected for plasma homocystine and total serum cholesterol levels from venous blood to study the association. Statistical analysis: Data analysis was done using Chi-square test. The outcome of analysis was presented as Chi-square score, df and p value to find out association. The ‘p’ value of less than 0.05 (*p
Keywords: Homocystine; Serum cholesterol; Acute ischemic stroke; Risk factor; Screening test